Preparing quality teachers : advances in clinical practice - Polly, Drew, 1977-; Garin, Eva (Emerald Publishing Limited : Information Age Publishing, Inc, 2022)
"National and international teacher education organizations and scholars have called for an increased emphasis on clinical practice in educator preparation programs. These recommendations include specific efforts to increase the duration, diversity, and quality of experiences that teacher candidates engage in during their time in P-12 schools while earning their teaching license. This book includes a robust set of chapters that include conceptual, theoretical, and empirical chapters related to innovative approaches in clinical practice in educator preparation. Authors include teacher educators from around the United States and Canada from a variety of types of higher education institutions. The book provides readers with examples, evidence, and ideas to thoughtfully consider their future direction in examining, planning, and implementing clinical practice experiences for teacher candidates"--